Forensic Features and Population Genetic Structure of Dong, Yi, Han, and Chuanqing Human Populations in Southwest China Inferred From Insertion/Deletion Markers - Liu, Yubo; Zhang, Han; He, Guanglin; Ren, Zheng; Zhang, Hongling; Wang, Qiyan; Ji, Jingyan; Yang, Meiqing; Guo, Jianxin; Yang, Xiaomin; Sun, Jin; Ba, Jinxing; et al. (Frontiers in Genetics, 2020)
Guizhou Province in Southwest China has abundant genetic and cultural diversities, but the forensic features and genetic structure of Guizhou populations remain poorly understood due to the sparse sampling of present-day populations. Here, we present 30 InDels data of 591 human individuals collected from four populations Dong, Yi, Han, and Chuanqing residing in Guizhou. We calculated the forensic parameters of 30 InDel loci and found this panel meets the efficiency of forensic personal identification based on the high combined power of discrimination, but it could only be used as a complementary tool in the parentage testing because of the lower combined probability of exclusion values. The studied populations are genetically closer related to geographically adjacent or linguistically related populations in southern China, such as the Tai-Kadai and Hmong-Mien speaking groups. The unrecognized ethnic Chuanqing people show an additional genetic affinity with Han Chinese, highlighting the role of possible military immigrations in their origin.